2015
DOI: 10.1007/s12011-015-0466-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Exercise-Induced Changes in Plasma Trace Element and Hormone Levels During Incremental Exercise in Well-Trained Athletes

Abstract: This study analyzes the relationship between hormonal changes induced by exercise and variations in trace elements associated with oxidative stress during incremental exercise. Nineteen well-trained endurance athletes performed a cycle ergometer test: after a warm-up of 10 min at 2.0 W kg(-1), workload increased by 0.5 W kg(-1) every 10 min until exhaustion. The analysis was controlled for prior diet and activity patterns, levels of exercise training, and time of day (circadian rhythms). Whole blood lactate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Trace minerals (TMs) are elements that are necessary for the human body due to the large number of biological functions in which they could be directly or indirectly involved during different physiological processes that can be altered as adaptation mechanisms to endurance exercise [15]. Essential trace minerals such as copper (Cu), manganese (Mn), selenium (Se), and zinc (Zn) act as cofactors of antioxidant enzymes to protect the body from oxygen free radicals [16].…”
Section: Introductionmentioning
confidence: 99%
“…Trace minerals (TMs) are elements that are necessary for the human body due to the large number of biological functions in which they could be directly or indirectly involved during different physiological processes that can be altered as adaptation mechanisms to endurance exercise [15]. Essential trace minerals such as copper (Cu), manganese (Mn), selenium (Se), and zinc (Zn) act as cofactors of antioxidant enzymes to protect the body from oxygen free radicals [16].…”
Section: Introductionmentioning
confidence: 99%
“…The results differ slightly. It can be seen that the measurements did not show a change in the level of plasma cobalt (Soria, 2016) during intense exercise in professional athletes. There is also no unambiguous information that the increase in cobalt concentration in the urine was the result of impaired renal function during prolonged exercise.…”
Section: Output Values Immediately After the Runmentioning
confidence: 70%
“…Considering the comparison of the results from the above studies (Buchman, 2013, Svyatova, 2013, Arakawa, 2016, Soria, 2016, Jablan, 2017 it can be concluded that the level of excretion of minerals and trace elements in urine depends largely on the type of performed sport, its duration and level of training of the participants, as well as individual characteristics of the body, which in turn leads to heterogeneous results.…”
Section: Output Values Immediately After the Runmentioning
confidence: 99%
“…Similarly, exercise of various intensity did not affect Co plasma levels. Moreover, no significant changes were observed in 7 minutes after exercise (Soria et al, 2016). Similarly, no significant difference between pre-and post-exercise salivary Co levels was detected in volunteers performing a cycle ergometer test (Chicharro et al, 1999).…”
Section: Cobalt Status In Athletesmentioning
confidence: 76%